Avaliação do potencial antioxidante dos extratos aquoso e etanólico de Mentha pulegium, Uncaria tomentosa e Phyllanthus niruri frente às alterações induzidas por T-butil hidroperóxido em eritrócitos humanos in vitro - Galvão, Dennyura Oliveira (2016)
The stone cruscher (Phyllanthus niruri), cat'sclaw (Uncaria tomentosa) and pennyroyal (Mentha pulegium)have been used by people to treat a variety of diseases associated with oxidative stress. In this study, we aimed to investigate the possible protective effects of aqueous and ethanolic extracts of Phyllanthus niruri, Uncaria tomentosa and Mentha pulegium against oxidative damage induced by tert-Butyl hydroperoxide (T-BHP) in human erythrocytes. The extracts (aqueous and ethanolic) of each plant (10-1000 μg/mL) was incubated in the presence and/or absence of the oxidative stress inducer, T-BHP (4 mM). Following exposure, oxidative stress parameters including lipid peroxidation, non-protein thiol (NPSH), osmotic fragility were assessed. Our results demonstrated that co-incubation of aqueous or ethanolic extract of P. niruri and U. tomentosa protect against T-BHP-induced peroxidation (i.e., TBARS formation) in human erythrocytes. However, extracts of both plants alone did not alter significantly the basal level of malondialdehyde when compared with the control (p > 0.05). M. pulegium also inhibited TBARS formation caused by T-BHP, which positively correlated with hemolysis and in some extend with NPSH. Besides, association of aqueous or ethanolic extract of M. pulegium with T-BHP potentiated NPSH oxidation and hemolysis of erythrocytesUnexpectedly, M. pulegium extracts significantly decreased NPSH levels when co-incubated with T-BHP. Similar unexpected results was the 100% hemolysis caused by P. niruri and U. tomentosa in the presence of T-BHP. . In conclusion, the co-treatment of aqueous and ethanolic extracts of P. niruri and U. tomentosa with T-BHP caused 100% hemolysis of human erythrocytes. Similarly, the association of aqueous and ethanolic extracts from M. pulegium with T-BHP left the erythrocytes more susceptible to hemolysis, which significantly correlated with NPSH oxidation, although it showed protective effect against lipid peroxidation induced by T-BHP.Taken together, our data shows for the first time the possible double face of these plants extracts. However, more studies are needed to further investigate and understand the mechanism(s) underlying the toxic effects resulting from the association of these plants extracts with the oxidative stressor, T-BHP.